Ser professor durante a pandemia: a relação dos saberes docentes no contexto de professores do Paraná - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The COVID-19 pandemic scenario has required many adaptations, from the use of alcohol and masks to mask, to social isolation measures, to prevent and avoid an increase in the number of people of infected people. This also had an impact on the education system, which began to the Emergency Remote Education (ERE) modality, an option that emerged in response to an emergency situation so that students would not miss the school year. These adaptations led the teachers to acquire new knowledge, which made them which led them to modify their work routine and encouraged the search for and exchange of knowledge. In order to understand these changes, this research aims to the main impacts and challenges faced by teachers in Paraná during this period faced by teachers in Paraná during this period of the COVID-19 pandemic. In conducting this research, we chose to look at these challenges in the light of Schon's concept of the Schon's concept of the reflective teacher, Tardif's teaching knowledge and Zabala's educational practice, as well as other authors who complement this vision. In this way, while respecting social isolation, data was collected by means of an electronic questionnaire, obtaining 505 responses. Of these, 377 were selected because we limited this investigation to teachers from the state of Paraná. This research was qualitative in nature, and we used content analysis to organize and analyze the data, we used content analysis to identify 11 categories. Our results indicate that the main impacts described by teachers were the lack of lack of training in the technologies available for Remote Learning and the quality of teaching, both of which teaching, both representing 34.4% of the responses found. Although we found other categories, it is possible to say that the impacts of the pandemic have related to the challenge of classes in the ERE modality, making teachers reflect on their own practice, re-signifying their knowledge and adapting their educational practice.
Keywords: Pandemia (COVID-19); Professor; Prática educativa; Saberes docentes; Educação; Pandemic (COVID-19); Teacher; Pedagogical Practice; Teaching knowledge; Education; CNPQ::CIENCIAS EXATAS E DA TERRA